If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18c + -29c = 151 + -30 Combine like terms: 18c + -29c = -11c -11c = 151 + -30 Combine like terms: 151 + -30 = 121 -11c = 121 Solving -11c = 121 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '-11'. c = -11 Simplifying c = -11
| 0.6x+1.5=-0.6(2x+5) | | 5(3x-1)+2x+9(2x-3)=5(6x-7)+11x-21 | | 4(-x-2)= | | 19-7p=-8p-(p-7) | | (7p-7)=10(2p+6)-7(-2+2p) | | 5x^4-8x^3-20x^2-4x+3=0 | | -6y+3x=-39 | | 4(y+2)-2(1-y)-4y=0 | | -33=2+5y | | 7(-2y+3)= | | 14+-2x=-3(x+1)-5 | | 55x+5y=45 | | 4(2x+5)+3x-2(x-7)=3(2x+7)-8 | | [Y]=5 | | -3x-2y=-2 | | 3(z-1)= | | 14-2x=-3(x+1)-5 | | 6(3+1)-30=3(2n-4) | | -6y+2y=-104 | | 4x-3+3=12 | | 9x-7=4x+9 | | 3x^2-5x+5=33 | | 10x-35+3x=5x-7a | | N+11=2 | | 2(3+x)=14x | | 11(4-3x)-5(2x+13)=194 | | -2y-42=-4(y+7) | | -2(y+9)= | | 5(c+2)=25 | | .4(12n-8)=26 | | 4(2x-7)=3(x+4) | | 2b+12b=70 |